An associated evaluation methodology of initial stress level of coal-rock masses in steeply inclined coal seams, Urumchi coal field, China. Issue 6 (5th March 2020) - Shan, Pengfei; Lai, Xingping
Abstract : Purpose: This paper aims to present an associated methodology to evaluate the initial stress of coal-rock masses in steeply inclined coal seams. Design/methodology/approach: On the basis of the real-time monitoring data in the field, the corresponding analytical analysis is carried out in consideration of the characteristics of topography and geology, so as to deduce the value of the initial stress in the study area and also give the analytical model of the initial stress field. Findings: The authors identified feasibility of the initial stress level of coal-rock masses in steeply inclined coal seams, and revealed that exact acquisition on the displacement of surrounding rock was feasible to analyze the initial stress level of coal-rock masses by the back analytical method in the steeply inclined coal seams as a two-dimensional plane problem. Originality/value: The calculation results including vertical stress, minimum horizontal principal stress and shearing stress were 7.057, 8.085 and 0.057 MPa, respectively. The KJ743 coal mine initial stress monitoring system was used to collect real-time initial stress data, which were used to check the accuracy of the analytical back results. The value of the vertical stress varied from 6.8 to 7.0 MPa, which is slightly smaller than the result of the back calculation. The minimum principal horizontal stress varied from 7.6 to 8.4 MPa, which is similar to the result of the back calculation.